SAT0501 THE IMPACT OF MORNING STIFFNESS ON THE DEFINITION OF INACTIVE DISEASE IN JUVENILE IDIOPATHIC ARTHRITIS. (June 2019) - Gicchino, Maria Francesca; Giancane, Gabriella; Alongi, Alessandra; Rosina, Silvia; Tibaldi, Jessica; Mazzoni, Marta; Ravelli, Angelo; Consolaro, Alessandro
Abstract : Background: Juvenile idiopathic arthritis (JIA) is the most common chronic rheumatic disease in childhood. Morning stiffness is a major symptom of JIA, and is usually associated with active disease. The 2004 preliminary criteria for inactive disease (ID) in JIA did not include the assessment of morning stiffness, whereas the 2011 revision of the criteria has allowed the presence of morning stiffness (MS) lasting ≤ 15 minutes. MS was included in 2011 revision based on the consideration that MS of a short duration (i.e., ≤ 15 minutes) can represent residua of previously active disease without current active disease. However, it is unclear whether the disease status of children with ID who have or do not have morning stiffness is comparable. Objectives: To compare the disease status of children with JIA who met the 2004 and 2011 revised criteria for ID in relation to the presence or absence morning stiffness. Methods: A database of 1208 Italian children included in 2 multicenter studies (1, 2) who underwent a total of 3380 visits was examined to identify all visits in which the patients fulfilled the 2004 or 2011 criteria for ID. In case a patient met the ID criteria in more than 1 visit, only the first visit was retained. For each visit with ID, the duration of morning stiffness was categorized as ≤ 15 min or > 15 min. Clinical assessments included demographic features and parent-reported outcomes Results: A total of 668 visits in which patients met the criteria for ID were identified. Absence of morning stiffness was reported in 564 (84.4%) visits, whereas in 104 visits (15.5%) there was morning stiffness. Among the visits with morning stiffness, in 55 (8.2%) duration was ≤15 min, and in 49 (7.3%) duration was > 15 min. The table shows the comparison of disease duration and parent-reported outcomes between patients with absence or presence of morning stiffness. MS: morning stiffness; IQR: interquartile range, *above the mean of healthy children (2) Conclusion: Among patients who met the 2011 criteria for ID, those with morning stiffness ≤15 min had worse parent-reported outcomes than those without morning stiffness. This finding suggests that parents may not perceive their child's disease state as true remission when lower degrees of morning stiffness are present. Notably, a sizeable proportion (7, 3%) of children meeting the 2004 ID criteria had morning stiffness lasting > 15 min. The removal of the criterion "Duration of morning stiffness of ≤ 15 minutes" to "Absence of morning stiffness" in the definition for ID should be considered. References: [1] Filocamo, et al. A new approach to clinical care of juvenile idiopathic arthritis: the Juvenile Arthritis Multidimensional Assessment Report. J Reumatol 2011 [2] Verazza, et al. Disease status, reasons for discontinuation and adverse events in 1038 Italian children with juvenile idiopathic arthritis treated with etanercept. PROJ 2016 Disclosure of Interests: Maria Francesca Gicchino: None declared, Gabriella Giancane: None declared, Alessandra Alongi: None declared, Silvia Rosina: None declared, Jessica Tibaldi: None declared, Marta Mazzoni: None declared, Angelo Ravelli Grant/research support from: Angelini, AbbVie, Bristol-Myers Squibb, Johnson & Johnson, Novartis, Pfizer, Reckitt Benkiser, and Roche, Consultant for: Angelini, AbbVie, Bristol-Myers Squibb, Johnson & Johnson, Novartis, Pfizer, Reckitt Benkiser, and Roche, Speakers bureau: Angelini, AbbVie, Bristol-Myers Squibb, Johnson & Johnson, Novartis, Pfizer, Reckitt Benkiser, and Roche, Alessandro Consolaro Grant/research support from: AbbVie, Pfizer,